PERENCANAAN PENDIDIKAN DALAM MANAJEMEN MUTU SEKOLAH DASAR - Purwati, Purwati; Yusuf, Mohammad Andi; Nyoman M, Ngurah Ayu (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This study aims to analyze the role of education planning in primary school quality management. Educational planning is a strategic step that includes the process of preparing the vision, mission, goals and program implementation to improve the quality of education. In the context of primary schools, effective education planning can ensure the achievement of the set quality standards through the optimization of human resources, infrastructure and integrated management systems. This research used a qualitative method with a case study approach in several primary schools. The results show that structured, participatory and data-based education planning has a significant impact on improving school quality, both in terms of student academic achievement, teacher professionalism and stakeholder satisfaction. The implications of this research emphasize the importance of collaboration between principals, teachers, parents and communities in developing education planning that is oriented towards sustainable quality.